Nanoparticle shape effect on the natural-convection heat transfer of hybrid nanofluid inside a u-shaped enclosure - Asmadi, Muhammad Solleh (Vinca Inst Nuclear Sci, 2022)
The effect of nanoparticle shape on the natural-convection heat transfer of Cu-Al2O3-water hybrid nanofluid inside a U-shaped enclosure is presented in this paper The governing equations are transformed into the dimensionless form using dimensionless variables. A three-node triangular finite element method is used with the Arewton-Raphson method to solve the problem numerically. The streamlines and isotherms as well as the local and average Nusselt numbers are presented for the fluid-flow with Rayleigh number of 10(4) to 10(6). It is found that blade nanoparticle shape produces the highest heat transfer rate while sphere is the lowest.